2014
DOI: 10.1371/journal.pone.0100628
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Long-Form Aromatase mRNA in the Male and Female Rat Brain

Abstract: In vitro studies show that estrogens acutely modulate synaptic function in both sexes. These acute effects may be mediated in vivo by estrogens synthesized within the brain, which could fluctuate more rapidly than circulating estrogens. For this to be the case, brain regions that respond acutely to estrogens should be capable of synthesizing them. To investigate this question, we used quantitative real-time PCR to measure expression of mRNA for the estrogen-synthesizing enzyme, aromatase, in different brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 47 publications
4
56
1
Order By: Relevance
“…The amount of enzyme and its activity are heterogeneously distributed and the many variables controlling both of these aspects remain poorly understood (Charlier et al, 2013; Jacobson et al, 1997; Tabatadze et al, 2014). Nonetheless there is great appeal in using estrogen mimetics as therapeutics given its potency at promoting both cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of enzyme and its activity are heterogeneously distributed and the many variables controlling both of these aspects remain poorly understood (Charlier et al, 2013; Jacobson et al, 1997; Tabatadze et al, 2014). Nonetheless there is great appeal in using estrogen mimetics as therapeutics given its potency at promoting both cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…5-19.5 (E18.5-19.5) (Huhtaniemi, 1994;Scott et al, 2009); while in mice, the fetal testosterone peak occurs at E17-18 (O'Shaughnessy et al, 2006E17-18 (O'Shaughnessy et al, , 1998. Testosterone can be converted into estradiol in the CNS by the enzyme aromatase (Stanic et al, 2014;Tabatadze et al, 2014;Yague et al, 2010Yague et al, , 2008Yague et al, , 2004. Both steroids are able to regulate the differentiation of neurons and glial cells, generating sex differences in brain connectivity, structure and function (Dittrich et al, 2014;MacLusky and Naftolin, 1981;Sakakibara et al, 2013).…”
Section: Neurobiology Of Astrogliamentioning
confidence: 99%
“…Nevertheless, different studies have shown large variability in aromatase levels in some brain regions (Shimotakahara et al 2004;Tabatadze et al 2014) and one study has provided indirect evidence of the efficacy of E2 synthesis in the adult cerebellum of rodents (Hedges et al 2012). In addition, no clear information is available as to the significance of low aromatase expression in regions of the adult brain like the PCs of the cerebellum (Sakamoto et al 2003).…”
Section: Possible E2 Functions On Pf Plasticity In Adult Cerebellummentioning
confidence: 99%